Design of impressed current cathodic protection for steel immersed in freshwater - Ahdash, Abdelsalam I. S. (2010)
Impressed current cathodic protection (ICCP) and coating give the optimum protection against corrosion for steel immersed in freshwater. This project presents the results of a study on the effectiveness of coating, impressed current cathodic protection and different environment conditions in preventing corrosion of steel. Experimental tests were carried out on coated and bare steel plates with ICCP and without ICCP by immersing in stagnant and flowing freshwater for one month. The results demonstrated that for coated and bare steel with ICCP and different variable resistance, the values of the potential are sufficient to protect the bare and the coated steel -840mV to -875mV.For coated steel without ICCP immersed in stagnant freshwater the potential has changed from -702 mV to -630mV, but for the bare sample the change in potential was about -10mV this may be due to oxide layer formed on the metal surface. For coated steel without ICCP immersed in flowing freshwater the drop in potential was about -50mV and the bare steel with the same condition was about -100 mV. A good agreement was observed for corrosion rate between weight loss measurement (4.29 mpy) test and electrochemical test (4.27 mpy) for bare steel in stagnant freshwater. The location of the reference electrode has significant implications for the control the potential change of ICCP system, the corrosion potential increases at the top of the sample (60cm below the water) and decrease when the sample was immersed further down to 1 meter in the water level.